On the role of the public interest in administrative law and judicial proceedings - Yegezhanova, D.R.; Saktaganova, I.S.; Juchnevicius, E. (Bulletin of the Karaganda University “Law Series”, 2025)
This article attempts to analyze the concept of public interest through the lens of scientific theories, international experience, and legislative practice. The study is a novelty in this field, as no similar review has been conducted within the framework of Kazakhstani administrative law and procedure. It has been identified that administrative discretion (the competence of an administrative body) serves as the primary mechanism for strengthening public interest. The effectiveness of this mechanism is supported by legislatively established administrative procedures and the ability to challenge public rights through litigation. The conducted analysis contributes to understanding the significance of legal protection of public interest and its benefits for the development of the legal system. The scientific value of the article also lies in examining the experience of administrative justice in Kazakhstan and other countries. By comparing the legal frameworks of developed states with that of Kazakhstan, it becomes evident that public interest is a legal construct that is difficult to regulate yet serves as a universal reference point for the development of legal systems. Therefore, the concept of public interest requires further clarification both for scientific comprehension and for broader interpretation and practical application. An additional value of the study is its systematic analysis of the concept of public interest in foreign legal doctrine, providing a foundation for further comparative legal research.